Justice Daniel Cohalan, 1865-1946 : American patriot and Irish-American nationalist - Doorley, Michael, 1957- (Book collections on Project MUSE., 2019)
"Justice Daniel Cohalan, or the 'Judge' as he became known, is best remembered today for his tempestuous relationship with Irish nationalist leader Éamon de Valera during the latter's visit to the United States in 1919-20. Cohalan deserves more attention than this and the story of his life as an American politician and Irish-American nationalist encapsulates the complex relationship between Irish America and Ireland during the early decades of the twentieth century. This biography examines Cohalan's background, his motivations and the wider social and political forces which shaped his Irish-American nationalism and American patriotism. As a senior member of the New York based Irish-American Clan na Gael, Cohalan played a significant role in the run-up to the 1916 Rising. Later, as leader of the 275,000-strong Friends of Irish Freedom, he became the spokesman for Irish-American nationalism during Ireland's War of Independence. Cohalan was also a key figure in American politics. He was chief advisor to New York's Tammany Hall leader Charles F. Murphy from 1906 to 1913 and was a close ally of Senator William Borah in the campaign against the League of Nations. Cohalan also formed a friendship with leading political figures in the Irish Free State such as Executive President William T. Cosgrave who in turn valued Cohalan's corporate and political connections. Cohalan's biography fills an important gap in Irish and American history and deepens our understanding of the phenomenon of Irish-American nationalism during a critical phase in the Irish revolutionary period"--